Pathways of change for achieving sustainability results: A tool to facilitate adaptive programming. Issue 3 (4th March 2022) - Bandali, Sarah; Style, Sarah; Thiam, Lamine; Omar, Omar Ahmed; Sabino, Alice; Hukin, Eleanor
ABSTRACT: Traditional approaches to development programming with fixed targets and outcomes do not fit complex problems where the pathway to achieve results differs in each context and evolves constantly. Adaptive programming improves responses to complex problems by identifying which solutions bring change. This paper reviews the theory behind adaptive programming approaches and introduces the 'Pathways of Change' tool for achieving sustainability results, developed for the multi-country Women's Integrated Sexual Health programme. Qualitative data, using semi-structured interviews and group discussions from teams in over 17 countries in Africa and South Asia, are presented which examine the application of the Pathways of Change (PoC) tool focusing on successes and challenges across different intervention areas. The PoC responds to the need for a more practical adaptive programming tool that can be tailored to support flexibility in global health programme implementation while meeting donor requirements. Findings suggest that the PoC tool provides a flexible yet robust alternative to traditional monitoring frameworks and is able to facilitate adaptive, contextualised planning and monitoring for multi-country programmes. The PoC tool offers a solution to realise the ambitions of implementing adaptive programming within global health programmes and potentially beyond.